Effectiveness Of Media Use Of Flipbook Learning Marzipan In The Cake Decoration Course On Students' Knowledge Level - Elsanti Mura Guna; Mahdiyah Mahdiyah; Annis Kandriasari (Jurnal Ilmiah Mandala Education (JIME), 2025)
The purpose of this study was to evaluate the impact or effectiveness of using flipbook learning media about Marzipan on increasing students' knowledge of Cake Decoration courses. The research method used was a quasi-experimental with a nonequivalent control group design, involving two comparison groups, namely: a control group (using PowerPoint) and an experimental group (using flipbook). The research instrument was 25 multiple-choice questions that had been tested for validity and reliability, as well as a student response questionnaire. Data were collected through pre-test, post-test, and questionnaire. Data analysis used the Wilcoxon test, the Mann Whitney test, and the N-Gain calculation. The results showed an increase in knowledge in both groups, but more significant in the experimental group. The Wilcoxon test showed that Zcount PowerPoint = 4.706 > Ztable 1.645 and flipbook = 4.782 > Ztable 1.645. The Mann Whitney test produced Zcount 2.183 > Ztable 1.656, indicating a significant difference between the groups. N-Gain analysis showed PowerPoint (0.52 in the moderate category) and flipbooks (0.78 in the high category). Student responses to the flipbooks were very positive, with an average of 95%. Thus, the Marzipan learning flipbooks effectively increased student knowledge while providing an interactive, enjoyable, and relevant learning experience.